“Sticky invasion” – the physical properties of Plantago lanceolata L. seed mucilage - Kreitschitz, Agnieszka; Kovalev, Alexander; Gorb, Stanislav N. (Beilstein Journal of Nanotechnology, 2016)
The mucilage envelope of seeds has various functions including the provision of different ways for the dispersal of diaspores. Chemical composition and water content of the mucilage yield particular adhesive and frictional properties in the envelope that also influence the dispersal of seeds. To determine the physical properties of Plantago lanceolata seed mucilage we studied (1) composition, (2) desiccation, (3) adhesion, and (4) friction properties of the mucilage under different hydration conditions. We revealed the presence of cellulose fibrils in the mucilage, which are responsible for a continuous and even distribution of the mucilaginous layer on the seed surface. The measured values of adhesive and frictional properties differed significantly in comparison to the previously studied pectic mucilage of Linum usitatissimum. Also, the water loss from the cellulose mucilage was more rapid. The obtained different values can result from the presence of cellulose fibrils and their interaction with pectins in the mucilage. Because of this feature the mucilage of P. lanceolata may represent a more regularly ordered and stabile system than the pectic mucilage of flax, which lacks cellulose. In spite of the fact that P. lanceolata mucilage revealed different adhesive and frictional properties than the pectic mucilage, it still demonstrates an effective system promoting zoochoric seed dispersal. Cellulose may additionally prevent the mucilage against loss from the seed surface.
Keywords: adhesion; cellulose mucilage; desiccation; friction; Plantago lanceolata

(untitled) - Grubert, M. (Acta Biol. Venez., 1974)

(untitled) - Ryding, O. (Syst. Geogr. Plants, 2001)

(untitled) - Yang, X.; Baskin, J. M.; Baskin, C. C.; Huang, Z. (Perspect. Plant Ecol. Evol. Syst., 2012)

(untitled) - Sagar, G. R.; Harper, J. L. (J. Ecol., 1964)

(untitled) - Cavers, P. B.; Bassett, I. J.; Crompton, C. W. (Can. J. Plant Sci., 1980)

(untitled) - Stewart, A. V. (Proc. N. Z. Grassl. Assoc., 1996)

The dispersal of plants throughout the world - Ridley, H. N. (1930. Reprint Bishen Singh Mahendra Pal Singh, Dehra Dun, 1990)

(untitled) - Bruun, H. H.; Poschold, P. (Oikos, 2006)

(untitled) - Mullan, J.; Percival, E. G. V. (J. Chem. Soc., 1940)

(untitled) - Percival, E. G. V.; Willox, I. C. (J. Chem. Soc., 1949)

(untitled) - Mühlethaler, K. (Exp. Cell Res., 1950)

(untitled) - Wojciechowska, B. (Monogr. Bot., 1966)

Functional surfaces in biology - Kreitschitz, A. (Biological Properties of Fruit and Seed Slime Envelope: How to Live, Fly, and Not Die, 2009)

(untitled) - Kreitschitz, A. (Seed Sci. Res., 2012)

(untitled) - Western, T. L. (Seed Sci. Res., 2012)

(untitled) - Haughn, G. W.; Western, T. L. (Front. Plant Sci., 2012)

(untitled) - Zykwinska, A.; Thibault, J.-F.; Ralet, M.-C. (J. Exp. Bot., 2007)

(untitled) - Caffal, K. H.; Mohnen, D. (Carbohydr. Res., 2009)

(untitled) - Scheller, H. V.; Ulskov, P. (Annu. Rev. Plant Biol., 2010)

(untitled) - Carpita, N. C.; Gibeaut, D. M. (Plant J., 1993)

(untitled) - Jarvis, M. C. (Plant, Cell Environ., 1984)

(untitled) - Burgert, I. (Am. J. Bot., 2006)

(untitled) - Köhler, L.; Spatz, H.-C. (Planta, 2002)

(untitled) - Donaldson, L. (Wood Sci. Technol., 2007)

(untitled) - McCann, M. C.; Wells, B.; Roberts, K. (J. Cell Sci., 1990)

(untitled) - Fujino, T.; Sone, Y.; Mitsuishi, Y.; Itoh, T. (Plant Cell Physiol., 2000)

(untitled) - Ha, M.-A.; Apperley, D. C.; Evans, B. W.; Huxham, I. M.; Jardine, W. G.; Viëtor, R. J.; Reis, D.; Vian, B.; Jarvis, M. C. (Plant J., 1998)

(untitled) - de la Paz Saldago-Cruz, M.; Calderón-Domíniguez, G.; Chanona-Pérez, J.; Farrera-Rebollo, R. R.; Méndez-Méndez, J. V.; Díaz-Ramírez, M. (Ind. Crops Prod., 2013)

(untitled) - Joelovich, M. (BioResources, 2008)

(untitled) - Prajapati, D. V.; Jani, G. K.; Moradiya, N. G.; Randeria, N. P. (Carbohydr. Polym., 2013)

(untitled) - Kreitschitz, A.; Kovalev, A.; Gorb, S. N. (Acta Biomater., 2015)

Praktikum z anatomii roślin - Braune, W.; Leman, A.; Taubert, H. (PWN, 1975)

(untitled) - Kreitschitz, A.; Vallès, J. (Flora (Jena), 2007)

(untitled) - Liesche, J.; Ziomkiewicz, I.; Schulz, A. (BMC Plant Biol., 2013)

Numerical methods of statistics - Monohan, J. F. (Cambridge University Press, 2001)

(untitled) - Voragen, A. G. J.; Coenen, G.-J.; Verhoef, R. P.; Schols, H. A. (Struct. Chem., 2009)

Current Protocols in Food Analytical Chemistry - Melton, L. D.; Smith, B. G. (Determining the Degree of Methylation and Acetylation of Pectin, 2001)

(untitled) - Wang, T.; Tohge, T.; Ivakov, A.; Mueller-Roeber, B.; Fernie, A. R.; Mutwil, M.; Schippers, J. H. M.; Persson, S. (Plant Physiol., 2015)

(untitled) - Cosgrove, D. J. (J. Exp. Bot., 2016)

(untitled) - Naran, R.; Chen, G.; Carpita, N. C. (Plant Physiol., 2008)

(untitled) - Macquet, A.; Ralet, M.-C.; Kronenberger, J.; Marion-Poll, A.; North, H. M. (Plant Cell Physiol., 2007)

(untitled) - Belton, P. S. (Int. J. Biol. Macromol., 1997)

(untitled) - Burgert, I.; Keplinger, T. (J. Exp. Bot., 2013)

(untitled) - De Lange, P. J.; Heenan, P. B.; Townsend, A. J. (N. Z. J. Bot., 2009)